Surface deformation monitoring and analysis of Southwest University of Science and Technology based on time series InSAR - Wei LU; Bin YANG; Kun YANG (Zhongguo dizhi zaihai yu fangzhi xuebao, 2023)
Taking Qingyi campus of Southwest University of Science and Technology as the study area, the surface deformation rate and time sequence variables of the study area from June 2017 to November 2020 were obtained by using SBAS-InSAR and PS-InSAR on 52 scene ascending Sentinel-1A radar images. Combined with coherence coefficient, deformation rate, variance and standard deviation, the results of two Time Series InSAR are tested and compared, and the mechanism and evolution process of surface deformation in the study area are discussed from two aspects of natural and human factors. The results show that there are many significant settlements in the study area, and the maximum vertical settlement rate can reaches 15 mm/a. The surface deformation is related to the factors such as student apartment buildings and road expansion. The surface settlement area is closely related to heavy rainfall, lithology and topography, and the stratigraphic boundary is not significantly related to the surface deformation. In general, the two monitoring results are generally consistent, and the monitoring results of SBAS-InSAR are more robust than PS-InSAR.